Pengembangan Ekonomi Kreatif Pada Masa Pandemi Covid-19 Dalam Perspektif Social Entrepreneurship - Aprillia Indah Pangestu (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This research was conducted to know the development of the creative economy during the Covid-19 pandemic, especially from the perspective of social entrepreneurship. The data in this study were obtained through a literature study. Based on data sourced from the 2020 Creative Economy OPUS report, it shows that the contribution of the creative economy sub-sector to the national Gross Domestic Product (GDP) reaches a value of IDR 1,211 trillion. Based on the 2019 Creative Economy Agency Performance Report, 17 sub-sectors are the focus of the development of the creative economy in Indonesia, where this development focuses on obtaining the best results, especially in the income sector. One of the steps that can be taken to develop the creative economy is through a waste bank by recycling inorganic waste. In managing it, if a waste bank has difficulties in funding, it can make a loan to one of the social entrepreneurships, namely Gandeng Tangan. During the current Covid-19 pandemic, the waste bank business is considered to have good potential. One of the products that can be produced from waste recycling is handicrafts or handicrafts, which are included in one of the sub-sectors of Indonesia's creative economy.